Distribution of temperature and salinity during recent oceanographic campaigns in the Eastern Tropical Pacific of Costa Rica. - Mora Escalante, Rodney E. (2020)
In Costa Rica, studies done in the Eastern Tropical Pacific or ETP are important because of their interaction/relationship with the Eastern Tropical Pacific Seascape, a known multinational conservation initiative. The present study describes the physical parameters of sea temperature and salinity around Cocos Island and its environment, the ETP, using CTD profiles. Methods: Data were obtained in April 2008, March 2009, April 2010, July 2011 and March 2012 near this island. Latitudinal and longitudinal transects were also done during October 2010 and March 2011 in a broader Costa Rican ETP region. In July 2012, three latitudinal transects were done around Cocos Island. Records were obtained using a CTD, measuring conductivity, temperature and pressure, among other variables. Results: Tropical Surface Water was observed in the upper 50m, showing temperatures above 25°C and salinities below 33psu. Below the surface waters, Subsurface Subtropical Water was detected below a 60m depth, showing temperatures colder than 25°C and salinities around 35psu. The transition between these waters was around 50-60m in depth. Temperature and salinity results were related with the atmosphere conditions observed, in which ETP variability was strongly influenced by the Inter Tropical Convergence Zone migration. Conclusions: This study also showed that reanalysis data from the HYCOM-NCODA general circulation model are comparable and in a good agreement with the CTD profiles. Temperature and salinity HYCOM data also reproduced, in general terms, the main characteristics of CTD data, having some small differences in the deeper levels. This reanalysis data set could also be used to study the tropical ocean dynamics, in wider ETP regions and for different seasons.